Degradation of methylene blue by dielectric barrier discharge plasma coupled with activated carbon supported on polyurethane foam. Issue 45 (20th August 2019) - Wu, Lihang; Xie, Qinglong; Lv, Yongbo; Zhang, Zhiyong; Wu, Zhenyu; Liang, Xiaojiang; Lu, Meizhen; Nie, Yong
Abstract : High dye degradation efficiency, COD removal and energy yield were obtained using a novel plasma reactor coupled with AC/PUF. Abstract : The degradation of methylene blue (MB) using a novel dielectric barrier discharge plasma reactor coupled with activated carbon supported polyurethane foam (AC/PUF) was investigated in this paper. The plasma reactor combining a glass bead-packed bed and a microporous plate was developed. The AC/PUF provided sufficient contact area between carbon media and pollutants and hence revealed a good MB removal capacity. The effects of input voltage and initial MB solution concentration on MB degradation efficiency were examined. Kinetic study indicated that plasma and AC/PUF in the coupled system had a good synergistic effect in MB degradation. The degradation efficiency of 100 ppm MB solution could reach 97.9% with 10 min treatment in the coupled system, which was close to that obtained by plasma treatment alone for 30 min (97.5%). The COD removal in the plasma and AC/PUF coupled system (90.7%) was much higher than that obtained by plasma treatment followed by AC/PUF adsorption (58.3%). In addition, the energy yield ( G 50 ) of the coupled system was up to 38.3 g kW −1 h −1, suggesting great energy efficiency of the system. Moreover, repeated use experiments of AC/PUF showed the good utilization potential of the coupled system. Finally, a possible degradation pathway of MB was proposed.